Relation of Obesity and Menarche Age among Adolescent Students - Shila Berenjy; Parichehr Hanachi (Tehran University of Medical Sciences, 2008)
Objective: The aim of this study was to investigate the relation between overweight and obesity among adolescent students and age of menarche. Materials and Methods: In a cross-sectional study 399 urban adolescent girls aged 11-14 years old were selected from schools of Kermanshah city in Iran. Anthropometric examinations including, triceps skin fold (TSF), mid arm circumference (MAC), body fat percentage (BF %), were measured and information on age of menarch and student's demographics were collected. Results: The results showed that age, body mass index (BMI) and menarche age were:12.63+1.01 year, 17.71+2.94 kg/m2 and 12.16+1.18 year respectively. Prevalence of overweight in respondents was 23.2%, however; prevalence of obesity was 23.2% for 11 years old , 22.4% for12 years olds , 24% of 13 years old  and 23.5% of 14 years old. Conclusion: There was a reverse relation  between BMI and age of menarche, however; it was not significant (p>0.1). This study suggests a high prevalence of obesity and relation between BMI and anthropometric parameters in adolesent girls.